GROWTH AND YIELD OF Shorea parvifolia PLANTED UNDER AKASIA PLANTS IN KAPUAS, CENTRAL KALIMANTAN - Wahyudi . (Departemen Silvikultur, Fakultas Kehutanan dan Lingkungan, Institut Pertanian Bogor (IPB), 2016)
Shorea parvifolia is the native species of Kalimantan and has a high commercial value. This research was aimed to analysis the growth and yield of meranti planted under Acacia mangium stands, as enrichment planting on the TPTI silvicultural system. The research was conducted at Kapuas District, Central Kalimantan Province. Type of soil at the site is ultisol with 2 606 mm/year of precipitation average. Initially, Acacia mangium planted with space namely 3 x 3 m at 1993. After two years, seedlings of Shorea parvifolia were planted among akasia plants with 1 111 tress/ha of density. Thinning of akasia plants were conducted stage by stage, especially at the stunted plants or dead. The data were latest analyzed at 2014 or at the moment of 20 years old. Research result showed that at the 1, 5, 10, 15, and 15 years old, life percentage of Shorea parvifolia are 94.8%, 78%, 66.4%, 57.5%, and 53% respectively. Average diameter of Shorea parvifolia at the same times are 1.27 cm, 6.13 cm, 12.8 cm, 19.86, and 27.46 cm respectively, and their average total height are 1.51 m, 5.27 m, 10.89 m, 17.18 m, and 24.41 m respectively. Volume growth of Shorea parvifolia at the same times namely 0.05 m3/ha , 3.97 m3/ha, 36.93 m3/ha, 145.44 m3/ha, and 303.62 m3/ha respectively.Key words: growth and yield, CAI, MAI, Shorea parvifolia.